2018
DOI: 10.1016/j.jcp.2018.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Eulerian–Lagrangian method for simulation of cloud cavitation

Abstract: We present a coupled Eulerian-Lagrangian method to simulate cloud cavitation in a compressible liquid. The method is designed to capture the strong, volumetric oscillations of each bubble and the bubble-scattered acoustics. The dynamics of the bubbly mixture is formulated using volume-averaged equations of motion. The continuous phase is discretized on an Eulerian grid and integrated using a high-order, finite-volume weighted essentially non-oscillatory (WENO) scheme, while the gas phase is modeled as spherica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 66 publications
(124 reference statements)
2
23
0
Order By: Relevance
“…The reported results provide useful quantitative data to predict the frequency, intensity and duration of pressure fluctuations experienced by very small particles that are passively transported by a turbulent flow. They can be used, for example, to inform modern models of numerical cavitation [25][26][27] . The behavior at higher Reynolds numbers and in other turbulent flows should certainly be explored to gain further understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The reported results provide useful quantitative data to predict the frequency, intensity and duration of pressure fluctuations experienced by very small particles that are passively transported by a turbulent flow. They can be used, for example, to inform modern models of numerical cavitation [25][26][27] . The behavior at higher Reynolds numbers and in other turbulent flows should certainly be explored to gain further understanding.…”
Section: Discussionmentioning
confidence: 99%
“…10, where the energy and temperature are averaged from each phase, as in Eq. 11and (12). The droplet is assumed to mix adiabatically and instantly when it impacts on the film, as calculated in Eq.…”
Section: Governing Equations For Discrete Phasementioning
confidence: 99%
“…Anez et.al (Anez et al, 2019) focused on the unresolved interface and tested the model against realistic experimental data, where indicated that models that are computationally less demanding and still accurate enough are required in an industrial environment. Maeda et.al (Maeda et al, 2018) presented a coupled Eulerian-Lagrangian method to simulate cloud cavitation in a compressible liquid for capturing the strong oscillations of each bubble. All these studies show the efficiency and promising application of the integrated discrete and continuous phase simulation approach.…”
Section: Introductionmentioning
confidence: 99%
“…We simulate the dynamics of bubbly-mixture using an Eulerian-Lagrangian method [9]. We discretize the governing equations on an axi-symmetric grid and integrate it using a finite volume, fifth-order WENO scheme.…”
Section: Numerical Setupmentioning
confidence: 99%
“…The simulation uses a coupled Eulerian-Lagrangian method for bubbly-liquid that can capture the dynamics of individual spherical bubbles and the fine structure of the pressure field. The numerical method and its validation have been described elsewhere [9]. We use the following two kinds of ultrasound wave: 1 cycle of a sinusoidal wave with a wavelength of 30 mm, and 10 cycles of a sinusoidal wave with a wavelength of 5 mm.…”
Section: Introductionmentioning
confidence: 99%